The Importance of Mathematical Game and Methods in the Formation of Mathematical Concepts in Primary Schools (Journal of Pedagogical Inventions and Practices, 2022)
In the following points, we will talk about the application of some of the interactive methods used in primary education practice in the teaching of mathematics.